Discoursing birthing care : experiences from Bangladesh - Afsana, Kaosar; Rashid, Sabina Faiz. (Dhaka : University Press, 2000)
Study on notions, practices and quality of birthing and health care in rural women of Bangladesh; comprises case studies.
Includes bibliographical references (pages [121]-124) and index.
BIED
Complimentary copy from BIED ; Complimentary copy from Kaosar Afsana, Professor, James P. Grant School of Public Health (JPGSPH), BRAC University
Keywords: Childbirth -- Bangladesh; Birth customs -- Bangladesh; Maternal health services -- Bangladesh; Bangladesh -- Social life and customs